Implementasi Agama dalam Membentuk Nilai dan Norma sebagai Alat Kontrol Sosial di Masyarakat - Yudi Apriansyah; Rany Claudia (Jurnal Sosiologi Nusantara, 2025)
Religion serves not only as a spiritual guide but also as a powerful mechanism of social control, shaping behavior and fostering social cohesion through internalized values and norms. In highly pluralistic societies such as Indonesia, understanding how diverse religious traditions shape social regulation is critical. However, comparative interfaith analyses remain scarce. This qualitative descriptive study investigates the role of religion as a tool of social control from an interfaith perspective in Bengkulu City, Indonesia. Ten religious leaders representing Islam, Catholicism, Protestantism, Hinduism, and Buddhism were selected through snowball sampling. Data were collected through in-depth, semi-structured interviews and analyzed using Miles, Huberman, and Saldaña's interactive model, within the framework of Kelman's Social Influence Theory. The findings indicate that all five religions promote core values—discipline, compassion, justice, and respect—that function as mechanisms of social regulation. Three key themes emerged: (1) moral discipline and self-regulation, (2) love and social harmony, and (3) ethical control and communal cohesion. These values are internalized through stages of compliance, identification, and internalization. While methods differ—from karmic beliefs in Hinduism to communal rituals in Islam—all traditions foster moral accountability and contribute to societal stability. Religion operates both vertically (between adherents and the divine) and horizontally (among community members), embedding both formal and informal social sanctions. Despite theological differences, shared moral imperatives strengthen interfaith understanding and reinforce social order. This study affirms the enduring relevance of religion in shaping ethical behavior in multicultural societies and calls for further exploration of its evolving role amid changing socio-political landscapes.